Timing of paediatric orchidopexy in universal healthcare systems: international administrative data cohort study. Issue 6 (24th July 2020) - Jay, M A; Arat, A; Wijlaars, L; Ajetunmobi, O; Fitzpatrick, T; Lu, H; Lei, S; Skerritt, C; Goldfeld, S; Gissler, M; Gunnlaugsson, G; Hrafn Jónsson, S; et al.
Abstract: Background: International guidelines in 2008 recommended orchidopexy for undescended testis at 6–12 months of age to reduce the risk of testicular cancer and infertility. Using administrative data from England, Finland, Ontario (Canada), Scotland and Sweden (with data from Victoria (Australia) and Iceland in supplementary analyses), the aim of this study was to investigate compliance with these guidelines and identify potential socioeconomic inequities in the timing of surgery before 1 and 3 years. Methods: All boys born in 2003–2011 with a diagnosis code of undescended testis and procedure codes indicating orchidopexy before their fifth birthday were identified from administrative health records. Trends in the proportion of orchidopexies performed before 1 and 3 years of age were investigated, as were socioeconomic inequities in adherence to the guidelines. Results: Across all jurisdictions, the proportion of orchidopexies occurring before the first birthday increased over the study period. By 2011, from 7·6 per cent (Sweden) to 27·9 per cent (Scotland) of boys had undergone orchidopexy by their first birthday and 71·5 per cent (Sweden) to 90·4 per cent (Scotland) by 3 years of age. There was limited evidence of socioeconomic inequities for orchidopexy before the introduction of guidelines (2008). Across all jurisdictions for boys born after 2008, there was consistent evidence of inequities in orchidopexy by the first birthday, favouring higher socioeconomic position. Absolute differences in these proportions between the highest and lowest socioeconomic groups ranged from 2·5 to 5·9 per cent across jurisdictions. Conclusion: Consistent lack of adherence to the guidelines across jurisdictions questions whether the guidelines are appropriate. Graphical Abstract: International guidelines recommend orchidopexy before 12 months of age. This study, using international administrative health data, found that this was achieved in only a minority of cases and that there were socioeconomic inequities in this outcome. Guidelines not widely applied